Literasi Keuangan, Uang Saku, Kontrol Diri, dan Teman Sebaya Terhadap Perilaku Menabung Mahasiswa - Mutiara Dalin Zulaika; Agung Listiadi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
The purpose of this research is to know the influence of financial literacy, pocket money, self-control, and peers both simultaneously and partially on the Accounting Education students Economics Faculty in State University of Surabaya. This type of research is quantitative research. The population in this study were Accounting Education students Economics Faculty in State University of Surabaya and sampling using purposive sampling technique so respondents became 174 respondents. Data collection techniques used were test and questionnaires. As for data analysis technique the researcher will used multiple linier regression analysis was done using SPSS 24.00. Based on the results of data analysis that has been done that both simultaneously and partially financial literacy, pocket money, self-control, and peers have a significant effect on behavior saving in Accounting Education students Economics Faculty in State University of Surabaya.